Materiality and Immateriality in Digital Art: Key Concepts for Understanding its Immanence - Mosqueda Gómez, Claudia (2019)
This article aims to demonstrate the way in which the digital work of art possesses immanent qualities between the material and the immaterial, operating on artistic expressions as univocal concepts. The material, tangible, reliable record of changes and transformations of the concrete; the immaterial: way of assuming the intangible of the work: behaviors, perceptions and forms of existence that operate in the world of the artistic as a power of objectivity without it still having a material substrate. Both forms of existence are presented in the objects and products of digital and interactive art through immanence.